2017
DOI: 10.1080/20964129.2017.1368873
|View full text |Cite
|
Sign up to set email alerts
|

Defining sustainable limits during and after intensification in a maritime agricultural ecosystem

Abstract: Introduction: Intensification of agricultural ecosystems in the 20th century proceeded by a series of innovations that initially ensured food security, but had negative consequences for the in-field and wider environments. A case study in the north Atlantic zone maritime cropland of the UK identified three phases: (1) reorganization between 1940 and 1960, (2) intensification leading to tripling of grain output (1960-1990), and (3) a leveling of output (1990-2015). Outcomes: Innovations that caused the changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Taken together, these tests demonstrated that in spite of reports that prolonged absence of legume cropping can result in a loss of Rlv diversity (Depret et al 2004) the CSC soils harboured a high diversity of effective Rlv capable of nodulating faba bean and pea. The maintenance of these relatively high and quite diverse Rlv populations may be the result of various factors including their persistence in the soil as saprophytes from legume-cropping prior to 1970 (although no record exists for the CSC sites, this cannot be excluded), but also legume weeds, including Vicia species, which were widespread in arable systems throughout the 20th century (Squire 2017), and invasion from adjacent sites (Hirsch 1996). In the case of the CSC, neighbouring farms were clearly a potential source as strains JHI981, JHI982 and JHI984 (from Carmichael and James Hutton Institute Farms) were included in the nodAD Group II that contained most of the CSC faba bean strains, as were pea strains isolated from fields neighbouring the CSC at Balruddery Farm.…”
Section: Lens Culinarismentioning
confidence: 99%
“…Taken together, these tests demonstrated that in spite of reports that prolonged absence of legume cropping can result in a loss of Rlv diversity (Depret et al 2004) the CSC soils harboured a high diversity of effective Rlv capable of nodulating faba bean and pea. The maintenance of these relatively high and quite diverse Rlv populations may be the result of various factors including their persistence in the soil as saprophytes from legume-cropping prior to 1970 (although no record exists for the CSC sites, this cannot be excluded), but also legume weeds, including Vicia species, which were widespread in arable systems throughout the 20th century (Squire 2017), and invasion from adjacent sites (Hirsch 1996). In the case of the CSC, neighbouring farms were clearly a potential source as strains JHI981, JHI982 and JHI984 (from Carmichael and James Hutton Institute Farms) were included in the nodAD Group II that contained most of the CSC faba bean strains, as were pea strains isolated from fields neighbouring the CSC at Balruddery Farm.…”
Section: Lens Culinarismentioning
confidence: 99%
“…Nitrogen inputs were then regulated downwards as a result of various EU directives and set‐aside, but the more so for grass than crops. Despite fluctuations due to these and other factors, Squire () estimated than total N inputs to crops were reduced to around 80% of those at the 1990 peak. Therefore, grain legumes began their decline in the 1800s, well before the intensification‐driven, steep rise in mineral N applications between 1950 and 1990; and the recent rise of grain legumes occurred during the period of level or regulated N input to arable crops.…”
Section: Resultsmentioning
confidence: 99%
“…Trends in areas occupied by grain legumes and in mineral nitrogen input appear unrelated ( Figure 1). Areas sown with beans and peas treated as grain crops declined after the first census in the 1850s reaching a low in the late 1930s, when together they occupied 0.23% of the area sown with arable F I G U R E 1 Trends in (a) legumes grown as crops, separated into areas sown with beans and peas treated as grain crops (heavy line to the left, 1854-1960), forage legumes (dashed), and later census categories of beans and peas after 1939 (marked "all types") including for grain, freezing and fresh products (gray line to the right), from various sources, mainly Agricultural Statistics Scotland (Materials and Methods); and (b) mineral nitrogen application to arable (tillage) crops and grass from Fertiliser Practice (2017), supplemented with projected trend from 1952 to 1971 estimated from earlier sources (e.g., Church & Lewis, 1977;Squire, 2017), and the horizontal dashed line indicating typical mineral N inputs preintensification (Paterson, 1925) | 5 of 15 SQUIRE Et al.…”
Section: Potential For Expansion-trends To Current Status and Distrmentioning
confidence: 99%
“…Although the model framework and case study presented here is designed to encompass key biophysical and economic elements of arable cropping systems, its flexible structure provides opportunities to incorporate social sustainability and life cycle analysis beyond the farm gate. These are important components in scaling up from cropping system to farm and multiple-farm or landscape level sustainability assessments [39,47]. Social sustainability could be included either as a third main branch or else through a social context pervading the existing branches.…”
Section: Discussionmentioning
confidence: 99%